Clinical implication of low estrogen receptor (ER-low) expression in breast cancer - Reinert, Tomás; Cascelli, Fanny; Resende, Cristiano Augusto Andrade de; Gonçalves, Aline Coelho; Godo, Vania Sanchez Prette; Barrios, Carlos Henrique (Frontiers in Endocrinology, 2022)
.Breast cancer is a heterogeneous disease, and the estrogen receptor (ER) remains the most important biomarker in breast oncology. Most guidelines set a positive expression threshold of 1% staining in immunohistochemistry (IHC) to define ER positivity. However, different expression levels may be associated with diverse degrees of sensitivity to endocrine therapy as ER expression may impact breast cancer molecular biology as a continuous variable. ER-lo tumors, defined as those with 1-10% ER expression, represent a relatively small subgroup of breast cancer patients, with an estimated prevalence of 2-7%. These tumors are similar to ERneg disease in their molecular landscape, clinicopathological characteristics, prognosis, and response to therapy. Nevertheless, a proportion may retain some degree of ER signaling dependency, and the possibility of responding to some degree to endocrine therapy cannot be completely ruled out. This review article discusses the most important considerations regarding the definition of ER positivity, pathology assessment, prognosis, and therapeutic implication of ERlo breast cancer from the medical oncology perspective.